Ritual Slaughter, Animal Welfare and the Freedom of Religion - Vellenga, Sipco (Journal of religion in Europe, 2015)
In 2011, the Dutch House of Representatives voted for the first time in its history for banning the practice of unstunned ritual slaughter in accordance to Jewish and Islamic rites. How should this remarkable vote be understood? In order to answer this question, a critical discourse analysis has been carried out. Three discourses are discerned in the debate: ‘unstunned ritual slaughter as an outdated practice,’ ‘ritual slaughter as a form of ritual torture’ and ‘unstunned ritual slaughter as a legitimate religious practice.’ The growing parliamentary support for the first two mentioned discourses is related to recent changes in the Dutch political landscape. In a wider context, it is related to a shift in the national self-conception of the Netherlands and, linked to that, to a change in the perceived position of traditional religious minorities within Dutch society in the aftermath of 9/11 and the ‘Fortuyn revolt.’